Artificial Life and Computational Intelligence - Chalup, Stephan (Springer, 2015)
This book constitutes the refereed proceedings of the First Australasian Conference on Artificial Life and Computational Intelligence, ACALCI 2015, held in Newcastle, NSW, Australia, in February 2015. The 34 revised full papers presented were carefully reviewed and selected from 63 submissions. The papers are organized in the following topical sections: philosophy and theory; game environments and methods; learning, memory and optimization; and applications and implementations.